Effects of Biochar on the Growth and Physiological and Mechanical Properties of Cucumber Plug Seedlings Before and After Transplanting - Guoxin Ma; Qiang Shi; Yuanchao Wu; Yang Liu; Lvhua Han; Jianping Hu; Hanping Mao; Zhiyu Zuo (Agriculture)
Since the characteristics of plug seedlings affect the effectiveness of automatic transplanting, this study aimed to explore the effect of the addition of biochar into substrates on the growth of plug seedlings before and after transplanting. The physicochemical properties of substrates with 0%, 5%, 10%, 15%, 20%, and 25% biochar addition all met the requirements of seedling cultivation. The growth trend, root systems, and mechanical properties of seedlings before transplanting and the leaf gas exchange parameters of seedlings after transplanting were measured in this study. The results indicated that the seedlings cultivated with 10% biochar added to the substrate achieved the best growth trend and physiological indices, and the root systems under this treatment were also stronger than those of other treatments, while the seedlings cultivated with 25% biochar treatment were the worst, with less than 22.23% of the growth seen in the 10% biochar treatment, and even less than 1.5% of the growth of the seedlings cultivated without biochar treatment. Since the strong root systems could enhance the mechanical properties of seedling pots, the seedling pots cultivated with 10% biochar added into the substrate possessed the best compression resistance properties, with the maximum value of 49.52 N, and could maintain maximum completeness after free-fall impacting, wherein the loss of root and substrate was only 8.22%. The analysis results of seedlings cultivated after impacting proposed that the seedlings with better growth trends and root systems before transplanting could obtain better leaf gas exchange parameters during the flower stage after transplanting, so the seedlings cultivated with 5%~10% biochar added into the substrate grew better after impacting and then transplanting. It was noticed that the seedlings cultivated with appropriate biochar added into the substrate were able to achieve the optimal growth parameters and mechanical properties before and after transplanting, which were better able to meet the requirements of automatic transplanting. Thus, this study can promote the development of automatic transplanting technology to some extent.